ANALISIS STRATEGI PESAN KREATIF PADA INSTAGRAM ADS AIRAS PASTRY - M Farrel Hakim; Sylvie Nurfebiaraning (Jurnal Komunikasi dan Bisnis, 2021)
Currently, one of the booming social media used as advertising media is Instagram. Until now, advertising is still considered the most effective and powerful way to inform or promote the product. An effective advertisement is said to be successful by creating and conveying a creative message strategy to get the maximum results. Creative message strategy used can be seen through The Facets Model of Effects are perception, cognitive, affective, persuasion, transformation, and behavior. In this case, Airas Pastry using the advertisement as a way of informing and promoting the products combining with the creative message strategy and Instagram Ads to reach the consumers more. This research with the title Analysis of Creative Message Strategies on Airas Pastry's Instagram Ads has purposes, which are to find out what is the creative message strategy on Instagram Ads Airas Pastry, how the creative messages on Instagram Ads can reach consumers more, and whether if the Instagram Ads can help spread creative messages. Also, this research method is using a qualitative method with the conclusion to find out how's the creative message strategy on Instagram Ads Airas Pastry, how it can reach the consumers more, and then whether if the Ads can help spread the creative message according to The Facets Model of Effects.